Dose calculations in a cell monolayer for high-throughput irradiation with proton beams generated by PW lasers for space applications. (November 2018) - Bobeica, Mariana; Aogaki, Sohichiroh; Asavei, Theodor; Cernaianu, Mihail O.; Ghenuche, Petru; Stutman, Dan
Abstract: One of the specific properties of laser-driven radiation is a broadband energy spectrum, which is also a feature of the space radiation fields. This property can be used in materials science studies or radiobiology experiments to simulate the energy spectrum of space radiation exposures in a ground-based laboratory. However, the differences in effects between the higher dose rates of laser generated radiation and the lower dose rates of space radiation have to be investigated in separate, prior studies. A design for a high-throughput irradiation experiment and the associated Monte Carlo dose calculations for a broadband energy proton beam depositing energy in a cell monolayer is presented. Dose control and dose uniformity in the cell monolayer was achieved in the simulations using a variable thickness Ni attenuator. A set of target doses from 0.2 Gy to 4 Gy was obtained and dose uniformity was optimized to less than 4% variability. This work opens the possibility of single or multiple exposures, controllable, high-throughput irradiation experiments on biological samples or materials, using broadband energy particle beams generated by lasers, with relevance for space applications.